2020
DOI: 10.1051/0004-6361/202038755
|View full text |Cite
|
Sign up to set email alerts
|

ALMA observations of transient heating in a solar active region

Abstract: Aims. We aim to investigate the temperature enhancements and formation heights of solar active-region brightenings such as Ellerman bombs (EBs), ultraviolet bursts (UVBs), and flaring active-region fibrils (FAFs) using interferometric observations in the millimeter (mm) continuum provided by the Atacama Large Millimeter/submillimeter Array (ALMA). Methods. We examined 3 mm signatures of heating events identified in Solar Dynamics Observatory observations of an active region and compared the results with synthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 103 publications
3
14
0
Order By: Relevance
“…Their typical duration was from about 55 to 125 s. Eklund et al (2020) reported that the properties of several of their events were consistent with the signatures of propagating shock waves (see also the simulations presented in Eklund et al 2021). Finally, we mention that transient brightenings in 3 mm ALMA observations of a small active region have been reported by da Silva Santos et al (2020). Their events corresponded to much higher excess brightness temperatures (up to about 14200 K) than the quiet Sun events of Paper II.…”
Section: Introductionsupporting
confidence: 64%
“…Their typical duration was from about 55 to 125 s. Eklund et al (2020) reported that the properties of several of their events were consistent with the signatures of propagating shock waves (see also the simulations presented in Eklund et al 2021). Finally, we mention that transient brightenings in 3 mm ALMA observations of a small active region have been reported by da Silva Santos et al (2020). Their events corresponded to much higher excess brightness temperatures (up to about 14200 K) than the quiet Sun events of Paper II.…”
Section: Introductionsupporting
confidence: 64%
“…UVBs (Peter et al 2014) are compact transient brightenings observed in UV bands, with very complex Si iv profiles, and do not generally show a co-spatial brightening in the coronal channels of the Solar Dynamics Observatory (SDO) Atmospheric Imaging Assembly (AIA) instrument. Similar targets have been studied with recent simulations (Danilovic 2017;Hansteen et al 2017Hansteen et al , 2019Libbrecht et al 2020) and observations (Socas-Navarro et al 2006;Toriumi et al 2017;Libbrecht et al 2017;Guglielmino et al 2018;Smitha et al 2018;Vissers et al 2019;Yadav et al 2019;Ortiz et al 2020;da Silva Santos et al 2020). Microflares or stronger events show a visible response in coronal channels and they would originate from or extend into higher layers.…”
Section: Introductionmentioning
confidence: 62%
“…Our inversion is not sensitive to temperatures above approximately 10,000 K so we cannot set constraints on the height where the heating observed in AIA is located. A coronal response is not normally seen in photospheric/low-chromospheric reconnection events such as Ellerman bombs, but heating to transition-region temperatures in reconnection events higher in the chromosphere can give a response in AIA if the column density of overlying cool material is low enough so that not all radiation is absorbed in the hydrogen and helium continua (Young et al 2018;Guglielmino et al 2019;Hansteen et al 2019;da Silva Santos et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ALMA intensity can be interpreted as brightness temperature under the Rayleigh-Jeans limit (Wedemeyer et al 2016). Hence, ALMA is a valuable tool to study the thermal structure of the chromosphere (some recent results include Shimojo et al 2017;Loukitcheva et al 2019;da Silva Santos et al 2020).…”
Section: Alma Observationsmentioning
confidence: 99%